Histoarchitecture of Uterus in Pre-pubertal and Post-pubertal Cats-Comparative Study - Dharani, P. (Indian Journal of Veterinary Anatomy, 2020)
The present study on histoarchitecture of the uterus in domestic short hair breed cat was carried outÂ during prepubertal and pubertal periods. The tissues were fixed in neutral buffered formalin and processed forÂ paraffin sectioning. The sections of 5-6Î¼m thickness were stained.